Performance optimization by musculoskeletal simulation - Rasmussen, J.; Holmberg, L. J.; Sørensen, K.; Kwan, M.; Andersen, M. S.; de Zee, M. (Science et motricité, 2012)
This paper uses two examples, from cross country skiing and badminton, to illustrate the idea of using musculoskeletal simulation as a tool to understand and ultimately optimize sports performance. The results show that the analysis provides insight into the performances that cannot be obtained by other means, and it is advocated that this insight ultimately can lead to better coaching. The importance of "know-why" over "know-how" is stressed, and it is hypothesized that this may enable athletes to learn difficult techniques faster.